2018
DOI: 10.2147/ott.s150952
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role of Gas6/Axl axis in solid malignancies: a meta-analysis and literature review

Abstract: BackgroundAxl is a receptor tyrosine kinase that is involved in many pathological conditions and carcinogenesis. Gas6 is the major ligand of Axl. Activation of Gas6/Axl pathway is essential for cancer development. However, its prognostic significance in solid tumors remains unclear. Therefore, we performed this meta-analysis to elucidate the prognostic impact of Axl.MethodsPublished studies on Axl or Gas6 expression and overall survival (OS) and/or disease-free survival (DFS) were searched from databases. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…Our investigation of the prognostic value of AXL and c-ABL indicated that high expression levels of these proteins in EAC patients were significantly associated with low patient survival and poor prognosis. Our results support the reports from other studies showing a strong association of AXL expression with poor prognosis in solid malignancies [24]. In addition, activation and overexpression of c-ABL have been associated with poor clinical outcome in solid tumors [13,25].…”
Section: Discussionsupporting
confidence: 92%
“…Our investigation of the prognostic value of AXL and c-ABL indicated that high expression levels of these proteins in EAC patients were significantly associated with low patient survival and poor prognosis. Our results support the reports from other studies showing a strong association of AXL expression with poor prognosis in solid malignancies [24]. In addition, activation and overexpression of c-ABL have been associated with poor clinical outcome in solid tumors [13,25].…”
Section: Discussionsupporting
confidence: 92%
“…AXL expression was found to be a poor prognostic marker for OS and disease‐free survival after complete resection of early‐stage NSCLC . In advanced NSCLC, PFS for EGFR‐TKI treatment tended to be shorter in patients with AXL expression scores of 3+ than in those with scores of 0 to 2+, although the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, AXL has emerged as a therapeutic drug target for TNBC treatment (65,66). In fact, AXL-CAR-T cell therapy in TNBC led to significant in vitro cytotoxicity and cytokine secretion as well as a reduction in tumor growth in an MDA-MB-231 xenograft mouse model (67).…”
Section: Receptor Tyrosine Kinase Axlmentioning
confidence: 99%